Impact of a patient-flow physician coordinator on waiting times and length of stay in an emergency department: A before-after cohort study. - Marta Morais Oliveira; Christophe Marti; Majd Ramlawi; François P Sarasin; Olivier Grosgurin; Pierre-Alexandre Poletti; Frédéric Rouyer; Olivier T Rutschmann (PLoS ONE, 2018)
OBJECTIVE:Overcrowding is common in most emergency departments (ED). Despite the use of validated triage systems, some patients are at risk of delayed medical evaluation. The objective of this study was to assess the impact of a patient-flow physician coordinator (PFPC) on the proportion of patients offered medical evaluation within time limits imposed by the Swiss Emergency Triage Scale (SETS) and on patient flow within the emergency department of a teaching urban hospital. METHODS:In this before-after retrospective cohort study, we compared the proportions of patients who received their first medical contact within SETS-imposed time limits, mean waiting times before first medical consultation, mean length of stay, and number of patients who left without being seen by a physician, between two periods before and after introducing a PFPC. The PFPC was a senior physician charged with quickly assessing in the waiting area patients who could not immediately be seen and managing patient flow within the department. RESULTS:Before introducing the PFPC position, 33,605 patients were admitted, versus 36,288 after. Introducing a PFPC enabled the department to increase the proportion of patients seen within the SETS-imposed time limits from 60.1% to 69.0% (p <0.0001). Waiting times until first medical consultation were reduced on average by 27.7 minutes (95% confidence interval [95% CI]: 25.9-29.5, p < .0001). No significant differences were observed as to length of stay or number of patients who left without being seen between the two study periods. CONCLUSIONS:Introducing a physician dedicated to managing patient flow enabled waiting times until first medical consultation to be reduced, yet had no significant benefit for patient flow within the ED, nor did it reduce the number of patients who left without being seen.